The African court: an ideal mechanism for the regional protection of human rights? - Olusanya, Olaolu (Centre for Law and Society, 2026)
Proposals for an African Court of human rights date back to 1961, when the African Conference on the Rule of Law, which brought together judges, teachers of law and legal practitioners from 23 African states, invited governments to consider the adoption of an African convention on human rights and the establishment of a court to safeguard the rights enshrined therein. After several attempts to adopt such a convention had failed, the idea of setting up a court was raised again in the late 1970s, when the African Charter on Human and Peoples' rights was negotiated. It was then on the ground that Africans preferred to settle disputes through negotiation and conciliation rather than through contentious proceedings, but the fear of many African they would be subjected to the judgments of an international body may have played a similar role.